Expressive Topics in Plastic Art Achievement A comparative study between Gustav Klimt and Star Kauusch (Al-Academy, 2023)
Schools and artistic trends derive their themes from artistic styles and styles as methods followed by the artist to express his themes embodied in the values of artistic and plastic elements as symbols and signs that can be described according to the type of art school and the extent to which the artist is influenced in employing them as a goal to achieve the plastic achievement in the painting, and from those vocabulary (human beings nature Life) as encoded messages that have an appearance and an interior, the appearance of which are forms, colors, formats and distributions of space and their interior meanings and semantics embody attitudes, events and circumstances that stem from the social depth and daily life and derive their components from those intellectual approaches to plastic art, including expressive arts, which simulate the insides of the artist and his sense of the direction of the surrounding subjects, and are presented in a formative style and an intellectual direction that has its aesthetic and semantic dimensions.